INFLUENCE OF CATALYST COMPOSITION ON DIVINYL YIELD IN THE CATALYTIC CONVERSION OF ETHANOL - D. S. Abdimurodova; N. I. Fayzullayev (European Science Publishing, 2025)
This study investigates the synthesis of highly active and productive catalysts for the conversion of ethanol to divinyl, along with an assessment of their physicochemical properties. The catalysts were synthesized based on mixed oxides of magnesium and aluminum, as well as zirconium-containing zeolites. Through hydrothermal methods and the use of various molecular sieves, catalyst samples with high sorption capacities were obtained. Their physicochemical properties were characterized using atomic emission spectrometry, X-ray phase analysis, and low-temperature nitrogen adsorption techniques. The catalytic activity and deactivation behavior of the catalysts were evaluated via the hydrogenation of crotonaldehyde. The results demonstrated that zirconium-based catalysts exhibit high selectivity and stability for divinyl production. From the perspective of economic efficiency and technological feasibility, zirconium-containing catalysts are identified as the most optimal for the catalytic synthesis of divinyl from ethanol.
Keywords: Ethanol, divinyl, catalyst, zirconium, iron and zinc oxides, mechanism, reaction yield.